노인이 지각한 건강에 대한 주관성 연구 - 정혜경(Hae Kyung Chung); 김경희(Kyung Hee Kim); 권혜진(Hye Jin Kwon); 윤은자(Eun Ja Yeun); 정연강(Yeoun Kang Chung) (지역사회간호학회지, 1999)
This study is to classify subjectification and the perceived health of the elderly according to Q-methodology and to provide basic materials for health promotion of the elderly. In this study, 28 elderly people residing in Seoul classified 33 selected statements in to 9 standards. The material taken from this process resulted in 4 types by the analysis using a PC QUANL program. Case 1 thought that religion was important for their health. Case 2 were go-getters they thought they felt healthy at work. Case 3 took a serious view of their relationships with other people. Case 4 centered around the couple, and thought it important to live with their life's companion.